1995
DOI: 10.1002/macp.1995.021960122
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optically active polymethacrylates with high glass transition temperatures

Abstract: A number of novel nonlinear optically (NLO) active polymethacrylates were prepared from the NLO active methacrylates 2a-d with azobenzene side groups and the bulky comonomer 1-adamantyl methacrylate. The polymers exhibit unusually high glass transition temperatures between 160 "C and 190°C. The copolymerization parameters of the monomer pair 1-adamantyl methacrylate (1)lDisperse red methacrylate 2 b (r, = 1,l t 0,2, r2 = 0,s f 0,2) show that the two monomers are incorporated almost statistically into the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 10 publications
0
10
1
Order By: Relevance
“…For copolymethacrylates prepared from NLO active methacrylates with azobenzene side groups and the bulky comonomer adamantyl methacrylate (T g 's 160 -190 8C) 49) , a r 33 value of 25 pm/V (measured at 633 nm) was found. Within 2 weeks, only a negligible decay of 7% of the EO effect was observed at room temperature.…”
Section: Polymethacrylatesmentioning
confidence: 99%
“…For copolymethacrylates prepared from NLO active methacrylates with azobenzene side groups and the bulky comonomer adamantyl methacrylate (T g 's 160 -190 8C) 49) , a r 33 value of 25 pm/V (measured at 633 nm) was found. Within 2 weeks, only a negligible decay of 7% of the EO effect was observed at room temperature.…”
Section: Polymethacrylatesmentioning
confidence: 99%
“…It is well known that side chains have significant influence on the thermal properties of polymers. Eckl et al reported that the T g of polymethacrylates increased from about 100 to 190°C by introducing bulky adamant substitutes onto the side chains 20 . N ‐(2,3‐epoxylpropyl)carbazole is a well known commercial monomer, which can be used for the preparation of photoconductive polymer 21–23.…”
Section: Introductionmentioning
confidence: 99%
“…Eckl et al . reported several copolymers of AdMA with nonlinear optically (NLO) active methacrylates, and Briers et al . also reported NLO active copolymers of AdMA with methylvinyl urethanes .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Acar et al synthesized poly(1-adamantylmethyl methacrylate) and poly [4-(1-adamantyl)phenyl methacrylate] by free radical polymerization and observed T g for both polymers. 8 Eckl et al reported several copolymers of AdMA with nonlinear optically (NLO) active methacrylates, 9 and Briers et al also reported NLO active copolymers of AdMA with methylvinyl urethanes. 10 In particular, a considerable number of studies have been conducted on copolymers of AdMA or its derivatives as photoresist materials.…”
Section: Introductionmentioning
confidence: 99%